Low-molar-concentration I + stabilizer / zinc salt aqueous zinc-iodine battery electrolyte and aqueous zinc-iodine battery
By using a low molar concentration of I+ stabilizer/zinc salt electrolyte in the aqueous zinc-iodine battery, and using a multi-iodine ion complexing agent and diluent to inhibit the side reaction and the shuttle effect of multi-iodine ions, the problems of high battery cost and short cycle life in the prior art are solved, and a water-type zinc-iodine battery with high Curlunary efficiency, long life and wide temperature range are achieved.
Patent Information
- Application Number
- CN202411723188.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing water-based zinc-iodine batteries require high molar concentration I+ stabilizer/zinc salt to achieve high Coulomb efficiency, resulting in an increase in battery cost, and there are side reactions and shuttle effects of multi-iodine ions during the cycle, affecting the battery life and working temperature range.
The electrolyte of the aqueous zinc-iodine battery with a low molar concentration of I+ stabilizer/zinc salt is used. The chemical components of the electrolyte include I+ stabilizer, other zinc salts, multi-iodine ion complexing agent, diluent and water. Through the combination of multi-iodine ion complexing agent and diluent, side reactions and shuttle effects of multi-iodine ions are inhibited.
Under the conditions of low molar concentration I+ stabilizer/zinc salt, a high-couloefficiency water-based zinc-iodine battery is achieved, which extends the battery cycle life and widens the working temperature range, so that the battery can operate stably under harsh conditions and reduces battery costs.
Smart Images

Figure CN119542575A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous zinc-iodine battery electrolytes, and particularly relates to a low molar concentration I + Aqueous zinc-iodine battery electrolyte and aqueous zinc-iodine battery containing stabilizer / zinc salt. Background Art
[0002] Energy and environment are two major issues that must be addressed for human survival and social development today. The development of next-generation battery technology is particularly important for the sustainable development of the environment and resources. At present, lithium-ion batteries dominate the market in the field of electrochemical energy storage. However, with the continuous increase in energy storage demand, the scarcity of lithium metal resources, the high cost of organic electrolytes and the flammable nature are becoming increasingly prominent, and there is an urgent need to develop safe and economical energy storage solutions. Aqueous zinc-iodine batteries based on reversible conversion between different iodine types have attracted global attention due to their advantages such as fast redox kinetics, good reversibility and the feasibility of multi-electron conversion. Aqueous zinc-iodine batteries are a new type of secondary battery developed in recent years. They have the advantages of high energy density, high power density, efficient and safe discharge process, non-toxic and cheap battery materials, and simple preparation process. They have high application value and development prospects in large-scale energy storage and other fields. However, most of the aqueous zinc-iodine batteries based on four-electron conversion reactions are based on high molar concentration I + Stabilizer / zinc salt can achieve high coulombic efficiency, which greatly increases the cost of the battery. Therefore, it is urgent to develop a method based on low molar concentration I + Stabilizer / zinc salt for high coulombic efficiency aqueous zinc-iodine batteries. Summary of the invention
[0003] In order to solve the problem that the existing aqueous zinc-iodine battery requires high molar concentration I + The present invention provides a low molar concentration I + Aqueous zinc-iodine battery electrolyte of stabilizer / zinc salt, wherein the electrolyte is at a low molar concentration I + The high coulombic efficiency of aqueous zinc-iodine batteries can still be achieved when the stabilizer / zinc salt is used, and the side reactions at the zinc negative electrode and the iodine positive electrode during the cycle of the aqueous zinc-iodine battery can be inhibited. - The shuttling effect of polyiodide ions and I2 / I2 conversion + In process + The hydrolysis of ions can extend the battery cycle life and broaden its operating temperature range, enabling it to operate stably under harsh conditions.
[0004] The present invention also provides a high coulombic efficiency wide temperature range aqueous zinc-iodine battery based on a four-electron conversion reaction.
[0005] The present invention is achieved through the following technical solutions:
[0006] The present invention provides a low molar concentration I + Aqueous zinc-iodine battery electrolyte of a stabilizer / zinc salt, wherein the chemical composition of the electrolyte comprises I + Stabilizer, other zinc salts, polyiodide ion complexing agent, diluent and water;
[0007] In the electrolyte, the I + The concentration of the stabilizer is 0.5 to 1.5 mol / L, the concentration of the other zinc salt is 0.5 to 2.5 mol / L, the mass fraction of the polyiodide ion complexing agent is 3 to 15%, and the volume ratio of the diluent to the water is 1:(3 to 19);
[0008] The polyiodide ion complexing agent includes at least one of polyvinyl alcohol, polyethylene glycol and polyvinyl pyrrolidone.
[0009] Furthermore, the diluent includes at least one of glycerol, dimethylacetamide and ethylene glycol monomethyl ether.
[0010] Furthermore, the I + Stabilizers include zinc chloride;
[0011] The other zinc salts include at least one of zinc perchlorate, zinc sulfate and zinc trifluoromethanesulfonate.
[0012] Preferably, in the electrolyte, the I + The concentration of the stabilizer is 1 mol / L, the concentration of the other zinc salts is 1.5 mol / L, the mass fraction of the polyiodide ion complexing agent is 6.14%, and the volume ratio of the diluent to the water is 1:5.66.
[0013] Based on the same inventive concept, the present invention provides a low molar concentration I + Application of stabilizer / zinc salt aqueous zinc-iodine battery electrolyte in the preparation of aqueous zinc-iodine batteries.
[0014] Based on the same inventive concept, the present invention provides an aqueous zinc-iodine battery, wherein the aqueous zinc-iodine battery comprises the above-mentioned low molar concentration I + Stabilizer / zinc salt for aqueous zinc-iodine battery electrolyte.
[0015] Based on the same inventive concept, the present invention provides a low molar concentration I + A method for preparing a stabilizer / zinc salt aqueous zinc-iodine battery electrolyte, the preparation method comprising:
[0016] Mix the diluent with water and then add I + stabilizer and other zinc salts to obtain a mixed solution;
[0017] A polyiodide ion complexing agent is added to the mixed solution, and then ultrasonic treatment is performed until the solution is uniform and transparent, so as to obtain a low molar concentration I + Stabilizer / zinc salt for aqueous zinc-iodine battery electrolyte.
[0018] Based on the same inventive concept, the present invention also provides a high coulombic efficiency wide temperature range aqueous zinc-iodine battery based on a four-electron conversion reaction, wherein the aqueous zinc-iodine battery uses an iodine composite material as a positive electrode, a glass fiber membrane as a diaphragm, and metal zinc as a negative electrode, and uses the above-mentioned low molar concentration I + Aqueous zinc-iodine battery electrolyte containing stabilizer / zinc salt is used as electrolyte.
[0019] Furthermore, the preparation method of the positive electrode is as follows:
[0020] Dispersing activated carbon and polyvinylidene fluoride in N-methylpyrrolidone to obtain a mixed slurry;
[0021] Dissolving potassium iodide and elemental iodine in water to obtain an iodine source solution;
[0022] The mixed slurry is coated on a current collector, dried, and then the iodine source solution is added dropwise to obtain a positive electrode.
[0023] Preferably, the mass ratio of the activated carbon to the polyvinylidene fluoride is 9:1, and the mass fraction of the activated carbon in the mixed slurry is 30%;
[0024] The molar ratio of the potassium iodide to the iodine element is 10:1, and the concentration of the potassium iodide in the iodine source solution is 1 mol / L;
[0025] The volume ratio of the mixed slurry to the iodine source solution is 25:1.
[0026] Based on the same inventive concept, the present invention also provides a zinc symmetrical battery, wherein the zinc symmetrical battery uses zinc sheets as the positive and negative electrodes of the battery, uses a glass fiber membrane as a separator, and uses the above-mentioned low molar concentration I + Aqueous zinc-iodine battery electrolyte containing stabilizer / zinc salt is used as electrolyte.
[0027] Based on the same inventive concept, the present invention also provides a zinc-copper asymmetric battery, wherein the zinc-copper asymmetric battery uses a zinc sheet as a negative electrode, a copper foil as a positive electrode, and a glass fiber membrane as a separator, and uses the above-mentioned low molar concentration I + Aqueous zinc-iodine battery electrolyte containing stabilizer / zinc salt is used as electrolyte.
[0028] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0029] 1. A low molar concentration I of the present invention +Aqueous zinc-iodine battery electrolyte containing a stabilizer / zinc salt, the electrolyte comprising I + The electrolyte is composed of a stabilizer, zinc chloride and other zinc salts, a polyiodide ion complexing agent, a diluent and water. + The four-electron conversion reaction (I - / I2 / I + ) high coulombic efficiency aqueous zinc-iodine battery, when the battery is working, the polyiodide ion complexing agent in the electrolyte can effectively inhibit the I - The shuttling effect of polyiodide ions and I2 / I2 conversion + In process + The presence of the diluent reduces the viscosity of the electrolyte and enables it to work normally at extremely low temperatures, thereby obtaining an aqueous zinc-iodine battery with excellent electrochemical performance, long cycle life and a wide operating temperature range (-40 to 40°C).
[0030] 2. A low molar concentration I of the present invention + Aqueous zinc-iodine battery electrolyte of stabilizer / zinc salt, wherein the electrolyte is at a low molar concentration I + The stabilizer / zinc salt can still achieve high coulombic efficiency aqueous zinc-iodine batteries, and can also inhibit the side reactions (hydrogen evolution and corrosion, etc.) occurring at the zinc negative electrode and the iodine positive electrode during the cycle of the aqueous zinc-iodine battery. - The shuttling effect of polyiodide ions and I2 / I2 conversion + In process + The hydrolysis of the electrolyte can prolong the battery cycle life and broaden its operating temperature range, enabling it to operate stably under harsh conditions. + The molar concentration of the stabilizer and zinc salt is very low, which can significantly reduce the cost of aqueous zinc-iodine batteries based on four-electron conversion reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 CV curves of Zn / / I2 full cells assembled with the electrolytes obtained in Example 1 and Comparative Example 1 of the present invention;
[0033] Figure 2The Zn / / I2 full battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention is subjected to a 1A g -1 Charge and discharge curves under current density;
[0034] Figure 3 The Zn / / I2 full battery assembled with the electrolyte obtained in Example 2 and Comparative Example 2 of the present invention is subjected to a 1A g -1 Charge and discharge curves under current density;
[0035] Figure 4 The Zn / / I2 full battery assembled with the electrolyte obtained in Example 3 and Comparative Example 3 of the present invention is subjected to a 1A g -1 Charge and discharge curves under current density;
[0036] Figure 5 The zinc symmetric battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention is at 1 mA cm -2 , 1mAh cm -2 Cycling performance diagram under current density;
[0037] Figure 6 This is a scanning electron microscope photograph of the zinc electrode surface of a zinc symmetrical battery assembled with the electrolyte obtained in Comparative Example 1 of the present invention after cycling;
[0038] Figure 7 This is a scanning electron microscope photograph of the zinc electrode surface of a zinc symmetric battery assembled with the electrolyte obtained in Example 1 of the present invention after cycling;
[0039] Figure 8 The surface XRD diagram of the zinc electrode surface of the zinc symmetric battery assembled with the electrolyte obtained in Example 1 of the present invention and Comparative Example 1 after cycling;
[0040] Fig. 9 The zinc symmetrical battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention is subjected to a high temperature of 40°C and a power of 1 mA cm -2 , 1mAh cm -2 Comparison of cycling performance under current density;
[0041] Fig.10 The zinc symmetrical battery assembled with the electrolyte obtained in Example 1 of the present invention is at a low temperature of -40°C, 1 mA cm -2 , 1mAh cm -2 Cycling performance diagram under current density;
[0042] Fig.11 The zinc-copper asymmetric battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention is subjected to 1 mA cm -2,0.5mAh cm -2 Cyclic Coulombic efficiency plots at current density;
[0043] Fig.12 The zinc-copper asymmetric battery assembled with the electrolytes obtained in Example 1 and Comparative Example 1 of the present invention is subjected to a high temperature of 40°C and a 1 mA cm -2 , 0.5mAh cm -2 Comparison of cycling performance under current density;
[0044] Fig.13 The zinc-copper asymmetric battery assembled with the electrolyte obtained in Example 1 of the present invention is subjected to a low temperature of -40°C and a 1 mA cm -2 , 0.5mAh cm -2 Comparison of cycling performance under current density;
[0045] Fig.14 The Zn / / I2 full battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention is subjected to a 2A g -1 Cycling performance diagram under current density;
[0046] Fig.15 The Zn / / I2 full battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention was subjected to high temperature of 40°C and 2A g -1 Cycling performance diagram under current density;
[0047] Fig.16 The Zn / / I2 full battery assembled with the electrolyte obtained in Example 1 of the present invention was subjected to a low temperature of -40°C and 1A g -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION
[0048] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0049] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0050] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0051] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0052] The technical principle of the present invention is as follows:
[0053] The present invention provides a low molar concentration I + Aqueous zinc-iodine battery electrolyte of a stabilizer / zinc salt, wherein the chemical composition of the electrolyte comprises I + Stabilizer, other zinc salts, polyiodide ion complexing agent, diluent and water;
[0054] In the electrolyte, the I + The concentration of the stabilizer is 0.5 to 1.5 mol / L, the concentration of the other zinc salt is 0.5 to 2.5 mol / L, the mass fraction of the polyiodide ion complexing agent is 3 to 15%, and the volume ratio of the diluent to the water is 1:(3 to 19);
[0055] The polyiodide ion complexing agent includes at least one of polyvinyl alcohol, polyethylene glycol and polyvinyl pyrrolidone.
[0056] In the present invention, I + The stabilizer can also provide a source of zinc to stimulate I2 to I + Conversion of Cl - , and other zinc salts can also be used as zinc sources, and various types of anions are introduced into the system to change the solvation environment around the zinc ions. + The four-electron conversion reaction of iodine can also be successfully achieved in the presence of a stabilizer.
[0057] In the present invention, the polyiodide ion complexing agent adopts at least one of polyvinyl alcohol, polyethylene glycol and polyvinyl pyrrolidone, which can effectively inhibit the shuttling effect of polyiodide ions. The mass fraction of the polyiodide ion complexing agent is 3-15%, which has the advantage of being able to effectively inhibit the corrosion of polyiodide ions without changing the electrolyte form. If the concentration is too high, the electrolyte viscosity will be too large, the ion conductivity will be too small, the battery polarization will increase, and the electrochemical performance will decrease; if the concentration is too low, the shuttling effect of polyiodide ions cannot be effectively inhibited.
[0058] In the present invention, the volume ratio of the diluent to water is 1:(3-19). If the volume ratio is too high, the electrolyte will be over-diluted and the conductivity will decrease.
[0059] Furthermore, the diluent includes at least one of glycerol, dimethylacetamide and ethylene glycol monomethyl ether.
[0060] In the present invention, the diluent is at least one of glycerol, dimethylacetamide and ethylene glycol monomethyl ether, which can effectively reduce the viscosity of the electrolyte and improve the ionic conductivity of the electrolyte.
[0061] Furthermore, the I + Stabilizers include zinc chloride;
[0062] The other zinc salts include at least one of zinc perchlorate, zinc sulfate and zinc trifluoromethanesulfonate.
[0063] In the present invention, I + The stabilizer uses zinc chloride, which is used as a zinc source and provides a catalyst that can stimulate I2 to I + Conversion of Cl - Other zinc salts use zinc perchlorate, zinc sulfate and zinc trifluoromethanesulfonate as zinc sources while providing diverse anions to change the solvation structure around zinc ions.
[0064] Based on the same inventive concept, the present invention provides a high coulombic efficiency wide temperature range aqueous zinc-iodine battery based on a four-electron conversion reaction, wherein the aqueous zinc-iodine battery uses an iodine composite material as a positive electrode, a glass fiber membrane as a diaphragm, and metal zinc as a negative electrode. + Aqueous zinc-iodine battery electrolyte containing stabilizer / zinc salt is used as electrolyte.
[0065] In the present invention, the high coulombic efficiency wide temperature range aqueous zinc-iodine battery based on the four-electron conversion reaction uses the iodine composite material as the positive electrode, which has the advantage of being able to provide an iodine source and serve as a site for iodine reaction, thereby effectively adsorbing iodine.
[0066] The following is a low molar concentration I of the present invention in combination with the embodiments and experimental data. + The aqueous zinc-iodine battery electrolyte and aqueous zinc-iodine battery of the stabilizer / zinc salt are described in detail.
[0067] The battery performance tests in the following embodiments all adopt the Xinwei battery test system. The assembly steps of the symmetrical battery include: using the zinc sheet polished with sandpaper as the positive and negative electrodes of the battery respectively, the glass fiber membrane as the diaphragm, and the electrolyte as the high coulomb efficiency wide temperature range aqueous zinc-iodine battery electrolyte prepared in the following embodiments, and assembling the battery into a 2032 button battery in an air environment. The assembly steps of the asymmetric battery include: using the polished zinc sheet as the negative electrode, the copper foil as the positive electrode, the glass fiber membrane as the diaphragm, and the electrolyte as the high coulomb efficiency wide temperature range aqueous zinc-iodine battery electrolyte prepared in the following embodiments, and assembling the battery into a 2032 button battery in an air environment. In the following embodiment, the assembly steps of the Zn / / I2 full battery include: using a zinc sheet polished with sandpaper as the negative electrode of the battery, mixing activated carbon and PVDF in a mass ratio of 90:10 and dissolving them in a solvent NMP to form a slurry, wherein the mass fraction of activated carbon in the slurry is 30%, and uniformly coating the slurry on the current collector hydrophilic carbon cloth, placing the hydrophilic carbon coated with activated carbon in an oven at 80°C for overnight drying, weighing 1.66g potassium iodide and 0.2538g iodine in a beaker, Add water and stir until dissolved, then add water to the 10mL mark, stir and sonicate to obtain an iodine source solution, drop a certain amount (10-50μL) of the iodine source solution onto a hydrophilic carbon cloth coated with activated carbon, use the obtained electrode sheet as the positive electrode, use the glass fiber membrane as the diaphragm, and use the electrolyte as the wide temperature range aqueous zinc-iodine battery electrolyte prepared in the following example. In an air atmosphere, assemble the battery into a 2032 button battery, and test the voltage range of 0.5V-1.85V vs Zn / Zn 2+ .
[0068] Example 1
[0069] This embodiment is a low molar concentration I + A method for preparing a stabilizer / zinc salt aqueous zinc-iodine battery electrolyte, comprising:
[0070] Step 1: 3 mL of glycerol and 17 mL of deionized water were measured, and then ultrasonicated and stirred until the solution was uniformly mixed to obtain a 15% volume fraction glycerol / water mixed solution;
[0071] Step 2: Weigh 2.7264 g of zinc chloride and 11.1714 g of zinc perchlorate hexahydrate into a beaker, stir the mixed solution obtained in step 1 until dissolved, then add 0.1 g of polyvinyl alcohol, heat and stir at 80°C until all the polyvinyl alcohol is dissolved in the solution, stir and ultrasonicate until the electrolyte is evenly dispersed to obtain a clear and transparent electrolyte.
[0072] Example 2
[0073] This embodiment is a low molar concentration I + A method for preparing a stabilizer / zinc salt aqueous zinc-iodine battery electrolyte, comprising:
[0074] Step 1: 3 mL of dimethylacetamide was measured, and then 17 mL of deionized water was measured, and then ultrasonic and stirred until the solution was mixed uniformly to obtain a 15% volume fraction dimethylacetamide / water mixed solution;
[0075] Step 2: Weigh 2.7264 g of zinc chloride and 8.6264 g of zinc sulfate heptahydrate into a beaker, stir with the water / mixed solution obtained in step 1 until dissolved, then add 0.1 g of polyethylene glycol, heat and stir at 80°C until all the polyvinyl glycol is dissolved in the solution, stir and ultrasonicate until the electrolyte is evenly dispersed to obtain a clear and transparent electrolyte.
[0076] Example 3
[0077] This embodiment is a low molar concentration I + A method for preparing a stabilizer / zinc salt aqueous zinc-iodine battery electrolyte, comprising:
[0078] Step 1: 3 mL of ethylene glycol monomethyl ether was measured, and then 17 mL of deionized water was measured, and then ultrasonic and stirred until the solution was mixed uniformly to obtain a 15% volume fraction ethylene glycol monomethyl ether / water mixed solution;
[0079] Step 2: Weigh 2.7264 g zinc chloride and 10.9058 g zinc trifluoromethanesulfonate in a beaker, stir with water / the mixed solution obtained in step 1 until dissolved, then add 0.1 g polyvinyl pyrrolidone, heat and stir at 80°C until all polyvinyl alcohol is dissolved in the solution, stir and ultrasonicate until the electrolyte is evenly dispersed to obtain a clear and transparent electrolyte.
[0080] Comparative Example 1
[0081] This comparative example provides a method for preparing an electrolyte, comprising:
[0082] Weigh 2.7264 g of zinc chloride and 11.1714 g of zinc perchlorate hexahydrate into a beaker, stir with deionized water until dissolved, and obtain a 1 M zinc chloride / 1.5 M zinc perchlorate solution.
[0083] Comparative Example 2
[0084] This comparative example provides a method for preparing an electrolyte, comprising:
[0085] Weigh 2.7264 g of zinc chloride and 8.6264 g of zinc sulfate heptahydrate into a beaker, and stir with deionized water until dissolved to obtain a 1 M zinc chloride / 1.5 M zinc sulfate solution.
[0086] Comparative Example 3
[0087] This comparative example provides a method for preparing an electrolyte, comprising:
[0088] Weigh 2.7264 g of zinc chloride and 10.9058 g of zinc trifluoromethanesulfonate into a beaker, and stir with deionized water until dissolved to obtain a 1 M zinc chloride / 1.5 M zinc trifluoromethanesulfonate solution.
[0089] Figure 1 The CV curves of the Zn / / I2 full battery assembled with the electrolytes obtained in Example 1 and Comparative Example 1 of the present invention. It can be seen from the figure that the addition of glycerol and polyvinyl alcohol does not participate in the reaction of the zinc-iodine battery, and by comparing the voltage difference between the oxidation peak and the reduction peak, it can be seen that the addition of polyvinyl alcohol additive can reduce the polarization of the iodine redox reaction.
[0090] Figure 2 The Zn / / I2 full battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention is subjected to 1Ag -1 The charge and discharge curves under current density. It can be seen from the figure that when the electrolyte is based on glycerol solvent and contains polyvinyl alcohol additive, the charge and discharge coulomb efficiency of the whole battery can reach 90.86%, while the charge and discharge coulomb efficiency of the whole battery without additive is only 80.93%.
[0091] Figure 3 The Zn / / I2 full battery assembled with the electrolyte obtained in Example 2 and Comparative Example 2 of the present invention is subjected to 1Ag -1 The charge and discharge curves under current density. It can be seen from the figure that when the electrolyte is based on dimethylacetamide solvent and contains polyethylene glycol additives, the charge and discharge coulomb efficiency of the whole battery can reach 84.21%, while the charge and discharge coulomb efficiency of the whole battery without additives is only 72.04%.
[0092] Figure 4 The Zn / / I2 full battery assembled with the electrolyte obtained in Example 3 and Comparative Example 3 of the present invention is subjected to 1Ag -1 The charge and discharge curves under current density. It can be seen from the figure that when the electrolyte is based on dimethylacetamide solvent and contains polyethylene glycol additives, the charge and discharge coulomb efficiency of the whole battery can reach 87.95%, while the charge and discharge coulomb efficiency of the whole battery without additives is only 74.19%.
[0093] Figure 5 The zinc symmetric battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention is -2 , 1mAhcm -2 Cycling performance diagram under current density. When the electrolyte is based on glycerol solvent and contains polyvinyl alcohol additive, the cycling stability of the zinc symmetric battery is better and has a longer cycle life. The battery assembled with an electrolyte based on 15% glycerol solvent and 0.1g polyvinyl alcohol additive has a stable cycle time of 1000h, while the control sample fails after less than 250h of cycling.
[0094] Figure 6 , 7 The scanning electron microscope photographs of the zinc electrode surface of the zinc symmetric battery assembled with the electrolytes obtained in Comparative Example 1 and Example 1 of the present invention after cycling. It can be seen from the figure that the electrolyte based on a certain volume fraction of glycerol and containing polyvinyl alcohol additive has a high conductivity at 1 mA cm -2 There is no obvious zinc dendrite on the surface of the zinc electrode that has been cycled for 50 hours at a current density of , and the zinc deposition is very uniform, deposited in a consistent direction, and very flat; while the surface of the zinc electrode based on glycerol solvent and additive-free electrolyte is unevenly deposited and very rough.
[0095] Figure 8 The surface XRD patterns of the zinc electrode surface of the zinc symmetric battery assembled with the electrolytes obtained in Example 1 and Comparative Example 1 after cycling. The electrolytes based on glycerol solvent and containing polyvinyl alcohol additives were used at 1 mA cm -2 There are significant differences in the zinc electrode after cycling for 50 h at a current density of 1.34 Å. When the electrolyte is based on glycerol solvent and contains polyvinyl alcohol additive, the peak value of byproducts on the zinc negative electrode surface is significantly reduced.
[0096] Fig. 9 The zinc symmetrical battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention is subjected to a high temperature of 40°C and a power of 1 mA cm -2 , 1mAh cm -2 Comparison of cycling performance under current density. It can be seen from the figure that the electrolyte containing polyvinyl alcohol additive based on glycerol solvent can stably cycle for 500 hours at a high temperature of 50°C. In contrast, the voltage of the symmetrical battery without additive electrolyte fluctuates violently in less than 50 hours and fails quickly. This shows that the prepared zinc-based double salt electrolyte containing additives has extremely strong tolerance to high temperature environment.
[0097] Fig.10 The zinc symmetrical battery assembled with the electrolyte obtained in Example 1 of the present invention is at a low temperature of -40°C, 1 mA cm -2 , 1mAh cm -2 Comparison of cycle performance under current density. As can be seen from the figure, even at a low temperature of -40°C, the symmetrical battery can work normally and stably cycle for 500h, indicating that the electrolyte has great tolerance to low temperature environment.
[0098] Fig.11 The zinc-copper asymmetric battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention is 1 mA cm -2 ,0.5mAh cm -2Cyclic Coulomb efficiency diagram under current density. When the electrolyte is based on a certain volume fraction of glycerol and contains polyvinyl alcohol additives, the zinc-copper asymmetric battery exhibits better cycle stability. The asymmetric battery assembled with an electrolyte based on 15% glycerol solvent and containing 0.1g polyvinyl alcohol additive can maintain a high coulomb efficiency of 99.80% and can be cycled for 1000 cycles. However, the asymmetric battery based on a glycerol solvent and an electrolyte without polyvinyl alcohol additives failed after 150 cycles, and its performance was significantly worse than that of an electrolyte based on a glycerol solvent and containing polyvinyl alcohol additives.
[0099] Fig.12 The zinc-copper asymmetric battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 was subjected to a high temperature of 40°C and a 1 mA cm -2 , 0.5mAh cm -2 Comparison of cycle performance under current density. It can be seen from the figure that the electrolyte containing polyvinyl alcohol additive based on glycerol solvent can stably cycle 500 cycles at a high temperature of 50°C. In contrast, the symmetrical battery of the electrolyte without additive fails in less than 150 cycles. This shows that the electrolyte of the present invention has extremely strong tolerance to high temperature environment.
[0100] Fig.13 The zinc-copper asymmetric battery assembled with the electrolyte obtained in Example 1 was subjected to a low temperature of -40°C and a power of 1 mA cm -2 , 0.5mAh cm -2 Comparison of cycle performance under current density. As can be seen from the figure, even at a low temperature of -40°C, the zinc-copper battery can work normally and stably cycle 500 times, indicating that the electrolyte has great tolerance to low temperature environments.
[0101] Fig.14 The Zn / / I2 full battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention is subjected to the conditions of room temperature and 2Ag -1 Cycling performance diagram under current density. It can be seen from the figure that when the electrolyte is based on glycerol solvent and contains polyvinyl alcohol additive, the full battery -1 It can stably cycle 1000 times at a current density of 1000 cycles, and the specific capacity after 1000 cycles is 413.77 mAh g -1 , the capacity retention rate is 92.44%, and the performance is significantly better than that of the full battery without additive electrolyte.
[0102] Fig.15 The Zn / / I2 full battery assembled with the electrolyte obtained in Example 1 and Comparative Example 1 of the present invention was subjected to high temperature of 40°C and 2A g -1Cycling performance diagram under current density. As can be seen from the figure, when the electrolyte is based on glycerol solvent and contains polyvinyl alcohol additives, the full battery can stably cycle 500 times with a capacity retention rate of 91.46%, while the full battery without additives has serious capacity decay at high temperatures. High temperature accelerates the growth of zinc electrode dendrites and the occurrence of side reactions. The rampant growth of dendrites and the accumulation of by-products lead to the eventual failure of the battery.
[0103] Fig.16 The Zn / / I2 full battery assembled with the electrolyte obtained in Example 1 of the present invention was subjected to a low temperature of -40°C and 1A g -1 Cycling performance diagram under current density. It can be seen from the figure that when the electrolyte is based on glycerol solvent and contains polyvinyl alcohol additive, the capacity retention rate of the full battery is 96.52% after 500 cycles, indicating that the electrolyte of the present invention has great tolerance to low temperature environment.
[0104] In summary, the aqueous zinc-iodine battery electrolyte prepared by the present invention can significantly inhibit the side reactions (hydrogen evolution and corrosion, etc.) occurring at the zinc negative electrode end and the iodine positive electrode end during the cycle of the aqueous zinc-iodine battery when constructing a wide temperature range aqueous zinc-iodine battery based on a four-electron conversion reaction. - The shuttling effect of polyiodide ions and I2 / I2 conversion + In process + The hydrolysis of , thereby extending the battery cycle life, and widening its operating temperature range, enabling it to operate stably under harsh conditions.
[0105] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0106] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0107] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A low molar concentration I + The aqueous zinc-iodine battery electrolyte of stabilizer / zinc salt is characterized by: The chemical composition of the electrolyte includes I + Stabilizer, other zinc salts, polyiodide ion complexing agent, diluent and water; In the electrolyte, the I + The concentration of the stabilizer is 0.5-1.5 mol / L, the concentration of the other zinc salt is 0.5-2.5 mol / L, the mass fraction of the polyiodide ion complexing agent is 3-15%, and the volume ratio of the diluent to the water is 1:(3-19); The polyiodide ion complexing agent includes at least one of polyvinyl alcohol, polyethylene glycol and polyvinyl pyrrolidone.
2. A low molar concentration I according to claim 1 + The aqueous zinc-iodine battery electrolyte of stabilizer / zinc salt is characterized by: The diluent includes at least one of glycerol, dimethylacetamide and ethylene glycol monomethyl ether.
3. A low molar concentration I according to claim 1 + The aqueous zinc-iodine battery electrolyte of stabilizer / zinc salt is characterized by: I + Stabilizers include zinc chloride; The other zinc salts include at least one of zinc perchlorate, zinc sulfate and zinc trifluoromethanesulfonate.
4. A low molar concentration I according to any one of claims 1 to 3 + Application of stabilizer / zinc salt aqueous zinc-iodine battery electrolyte in the preparation of aqueous zinc-iodine batteries.
5. An aqueous zinc-iodine battery, characterized in that: The aqueous zinc-iodine battery comprises a low molar concentration I + Stabilizer / zinc salt for aqueous zinc-iodine battery electrolyte.
6. A low molar concentration I according to any one of claims 1 to 3 + The method for preparing a stabilizer / zinc salt aqueous zinc-iodine battery electrolyte is characterized in that: The preparation method comprises: Mix the diluent with water and then add I + stabilizer and other zinc salts to obtain a mixed solution; A polyiodide ion complexing agent is added to the mixed solution, and then ultrasonic treatment is performed until the solution is uniform and transparent, so as to obtain a low molar concentration I + Stabilizer / zinc salt for aqueous zinc-iodine battery electrolyte.
7. A high coulombic efficiency wide temperature range aqueous zinc-iodine battery based on a four-electron conversion reaction, characterized in that: The aqueous zinc-iodine battery uses an iodine composite material as a positive electrode, a glass fiber membrane as a separator, and metal zinc as a negative electrode. + Aqueous zinc-iodine battery electrolyte containing stabilizer / zinc salt is used as electrolyte.
8. The high coulombic efficiency wide temperature range aqueous zinc-iodine battery based on four-electron conversion reaction according to claim 7, characterized in that: The preparation method of the positive electrode is as follows: Dispersing activated carbon and polyvinylidene fluoride (PVDF) in N-methylpyrrolidone to obtain a mixed slurry; Dissolving potassium iodide and elemental iodine in water to obtain an iodine source solution; The mixed slurry is coated on a current collector, dried, and then the iodine source solution is added dropwise to obtain a positive electrode; The mass ratio of the activated carbon to the polyvinylidene fluoride is 9:1, and the mass fraction of the activated carbon in the mixed slurry is 30%; The molar ratio of the potassium iodide to the iodine element is 10:1, and the concentration of the potassium iodide in the iodine source solution is 1 mol / L; The volume ratio of the mixed slurry to the iodine source solution is 25:
1.
9. A zinc symmetrical battery, characterized in that: The zinc symmetrical battery uses zinc sheets as the positive and negative electrodes of the battery, uses a glass fiber membrane as a separator, and uses a low molar concentration I + Aqueous zinc-iodine battery electrolyte containing stabilizer / zinc salt is used as electrolyte.
10. A zinc-copper asymmetric battery, characterized in that: The zinc-copper asymmetric battery uses a zinc sheet as a negative electrode, a copper foil as a positive electrode, and a glass fiber membrane as a separator. + Aqueous zinc-iodine battery electrolyte containing stabilizer / zinc salt is used as electrolyte.
Citation Information
Cited By
Positive electrode additive and electrolyte for high-stability two-electron aqueous zinc-iodine battery
CN121507139A
Two-component electrolyte additive and application thereof in zinc-iodine battery
CN121862901A